1981
DOI: 10.1083/jcb.91.2.414
|View full text |Cite
|
Sign up to set email alerts
|

Observations on intracellular pH during cleavage of eggs of Xenopus laevis.

Abstract: Direct measurements of intracellular pH was made with recessed-tip pH microelectrodes in fertilized eggs of the frog, Xenopus laevis, from approximately 1 h after fertilization to mid-blastula. The intracellular pH just before first cleavage was 7.65 +/- 0.04 (SD; n = 9). By stage 5 to the middle of stage 6, average intracellular pH was 7.70 +/- 0.06 (SD; n = 16). A statistically significant alkalization of 0.18 +/- 0.03 pH unit (SD; n = 5) was observed beginning in early blastula. A cycle of less than or equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…For example, pH gates gap junctions (Greenfield et al, 1990;Turin and Warner, 1980), which are essential for normal LR axis development (Levin and Mercola, 1999). pH regulation also has a role in gene expression and differentiation (Sater et al, 1994;Uzman et al, 1998) and in other important developmental processes such as proliferation, apoptosis and growth factor release (Bidani et al, 1998;Lee and Steinhardt, 1981;Putney and Barber, 2003;Shrode et al, 1997). pH also has other physiological effects that are likely to be important during development, although a direct connection has not been shown.…”
Section: Research Articlementioning
confidence: 99%
“…For example, pH gates gap junctions (Greenfield et al, 1990;Turin and Warner, 1980), which are essential for normal LR axis development (Levin and Mercola, 1999). pH regulation also has a role in gene expression and differentiation (Sater et al, 1994;Uzman et al, 1998) and in other important developmental processes such as proliferation, apoptosis and growth factor release (Bidani et al, 1998;Lee and Steinhardt, 1981;Putney and Barber, 2003;Shrode et al, 1997). pH also has other physiological effects that are likely to be important during development, although a direct connection has not been shown.…”
Section: Research Articlementioning
confidence: 99%
“…Experiments with early Xenopus embryos indicated, however, that pH, is not necessarily a universal regulator of mitosis. It was reported that even if small oscillations in pHi occurred during the mitotic cycle in early Xenopus embryos, no delay in mitosis occurred when the pHi was artificially reduced (Lee & Steinhardt, 1981). Furthermore, clamping at high pHi values did not interfere with normal chromosome cycling or cell division in the sea urchin embryo (Grainger et al, 1979).…”
Section: Effect Of Ph On Ion Conductivitiesmentioning
confidence: 99%
“…The rhythmicity of the pH, oscillations has been well characterized in Xenopus embryos [Lee and Steinhardt, 1981;Webb and Nuccitelli, 1982;Grandin and Charbonneau, 19901. Fertilization of Xenopus eggs is accompanied by a permanent increase in the intracellular pH followed by a periodic fluctuation in pH,.…”
Section: Ph Cycles In Living Cellsmentioning
confidence: 98%
“…Changes in intracellular pH (pH,) are associated with a variety of cellular growth control mechanisms [Busa, 1986;Roos and Boron, 1981;Rozengurt, 19861. For example, systematic changes in pH, occur during the cell cycle progression from interphase to mitosis [Gerson and Burton, 1977;Musgrove et al, 1987;Taylor and Hodson, 1984;Bright et al, 19871. The rhythmicity of the pH, oscillations has been well characterized in Xenopus embryos [Lee and Steinhardt, 1981;Webb and Nuccitelli, 1982;Grandin and Charbonneau, 19901. Fertilization of Xenopus eggs is accompanied by a permanent increase in the intracellular pH followed by a periodic fluctuation in pH,.…”
Section: Ph Cycles In Living Cellsmentioning
confidence: 99%